Pengaruh Potongan Harga pada Sistem Inventori (Q,R) yang Mempertimbangkan Ketergantungan antara Lot Size dan Lead Time - Nur Indrianti; Setya Prajoko; Trismi Ristyowati (Forum Teknik, 2006)
This paper is concerned with lot size dependent lead times in a (Q,R) inventory system considering-quantity discounts offered by suppliers. With regards to the existing model that considers the impact of lot size on lead time and safety stock equirements, we present an efficient iterative algorithm to decide lot size that minimizes total inventory cost. The algorithm simultaneously determines lot size and safety stock based on the tradeoff between inventory holding cost and shortage cost. A nurnerical example is provided to clarify the iteration procedure. In addition, we identify the effict of shop floor queing factor on lot size decision.The result of the study shows that purchasing larger lot size does not always result in minimum total inventory cost. Larger lot size reduces per unit ordering cost and shortage cost, but increases the holding cost due to more inventories. Moreover, we conclude that increased shop floor queuing factor leads to increased production lead time, resulting in larger lot size.Keywords: (Q,R) inventory system, lot size dependent lead times, quantity discount.